Effects of dietary live microbes intake on a newly proposed classification system for steatotic liver disease - Zhikun Dai; Zihong Bao; Hanyuan Lin; Qinglong Yang; Jingtao Huang; Xuan Zhang; Nan Luo; Haoxian Tang; Xiaohui Zhou (Scientific Reports, 2025)
Abstract Steatotic liver disease (SLD) is a common chronic liver disease without effective therapeutic options. Some studies suggest potential health benefits of dietary live microbes. This study aims to investigate the association between dietary live microbes intake and metabolic dysfunction-associated steatotic liver disease (MASLD) / metabolic alcohol-related liver disease (MetALD) / alcoholic liver disease (ALD) in adults. Data from the National Health and Nutrition Examination Survey 1999–2018 were analyzed. MASLD was defined according to the latest Delphi Consensus standard. Participants were grouped based on estimated dietary live microbe intake: low (< 104 CFU/g), moderate (104–107 CFU/g), and high (> 107 CFU/g). Multivariable logistic regression analysis was employed to assess the impact of dietary live microbes on MASLD/MetALD/ALD, along with further investigations into non-dietary probiotic/prebiotic relationships. Participants had a weighted mean age of 47.05 years (SE, 0.24) and 50.59% were female. MASLD proportions differ among low (21.76%), moderate (22.24%), and high (18.96%) microbe groups. Similarly, for MetALD, proportions are 7.75%, 6.95%, and 6.44%, and for ALD, 5.42%, 3.59%, and 2.97% in respective groups. The high dietary live microbe intake group was associated with a 16% lower risk of MASLD compared to those in the low intake group (trend test, P = 0.02), while the risk of ALD was reduced by 25% in the moderate intake group. A lack of association was identified between non-dietary prebiotic/probiotic and MASLD/MetALD/ALD. Our study suggests that a relatively high intake of live microbes diets in adults is associated with a lower risk of SLD.